RESPON TANAMAN KEDELAI (Glycine max (L.) Merril ) SEBAGAI TANAMAN SELA PADA KEBUN KELAPA SAWIT BELUM MENGHASILKAN (TBM) DENGAN APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN ABU BOILER - Ridwan Amali; Nelvia '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to studythe interaction of compostof oil palm empty bunches(OPEB) and bolier ash on growth and yield of soybeans as an intercrop on oil palm plantation. The research was conducted on oil palm plantation area Agriculture Faculty, Riau University carried out at Tampan Subdistrict, Municipality Pekanbaru, from February to May 2014. The research is factorial experiment 4 x 2 andused a randomized block design (RBD). The first factor is compost of OPEB with 4 levels (0, 5, 10 and 15 ton/ha) and second factor isboiler ash with 2 level (2.5 and 5 ton/ha). Eachof treatments combination repeated 3 times. The effect all of treatments combination has knowed by DNMRT test (Duncan's New Multiple Range Test) at 5% level. Parameters measured were plant height, flowering age, time of harvest, totally pods, pithy pod percentage, dry grain weight per plot and weight of 100 seeds. The result of the research showed that the application of compost of OPEB 10 tons/ha and boiler ash           5 ton/ha increased plant height, dried grain weight per plot and weight of100 seeds significantly compared with application boiler ash 2.5 tons/ha without compost of OPEB, but not significantly compared with other treatments. Keywords : soybean, compostof oil palm empty bunches,boiler ash